The comparison of attacking efficiency index (aei) derived from younger male and female seniors (U-23) participated at the national judo championship of Bosnia and Herzegovina - Drljevic, J.; Cutuk, H.; Kapo, S.; Vražalica, A.; Kapo, A.; Kajmovic, H. (Sportski Logos, 2020)
The main objective of this research is about to compare the attacking efficiency index (AEI) derived from younger male and female U-23 seniors, participated at The National Judo Championship of Bosnia and Herzegovina held in 2015 at Ilidza-Sarajevo. The sample of respondents consists (n=60) combats of younger male seniors and (n = 22) combats of younger female ones in all seven weight categories. The sample of variables consists of throwing techniques, parterre techniques and scored technical points as result of the quality of the throwing techniques and the techniques in the parterre being performed. The data were collected by video analysis of the combats from younger male and female seniors that participated at The National Judo Championship of Bosnia and Herzegovina. The results shown that there were not any differences in the points scored between the younger male and female seniors of U23. The results of the T-test for independent samples shown the existence of statistically significant differences in the cumulative attacking efficiency index, which was AEI = 10.9 at younger male seniors and AEI = 11.77 at younger female ones. The AEI results of the individual techniques shown that the most effective ones were at the younger male seniors named Kesa gatame, Tani otoshi and Uchi mata, and at the younger female seniors named O Soto Gari, Ouchi gari and Kesa gatame. The results suggested the need to re-analyze the performances from competitions of younger male and female seniors, as well as the recommendation for coaches to adjust their plans and programs of technicaltactical and fitness preparation of athletes, especially younger female seniors.